2018
DOI: 10.3329/bvet.v33i2.36460
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone concentration in surgically castrated Black Bengal goats

Abstract: The experiment was carried out to detect the blood serum testosterone concentration after orchiectomy in Black Bengal bucks (Capra hircus). Twelve apparently healthy bucks of 8 - 10 months old were randomly divided into two groups. Group A were castrated surgically through open uncover method and group B remained intact. Local analgesia (2% lidocaine hydrochloride) @ 0.5 mL per spermatic cord and 0.5 mL at the tip of each scrotum were applied initially in all bucks. After aseptic preparation, incision was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The resolution of the post castration inflammation and associated swelling indicates healing of damaged tissue and cessation of spermatogenesis provided that the castration was successful. Testosterone production is usually affected as was previously reported that testosterone concentration was significantly decreased from 6.1 ng/ml on the day of castration to 0.6 ng/ml 30 days later (Al-Asadi and Al-Kadi 2012; Hasan et al 2016). As was observed for the testes, the diameters of the left and right spermatic cords also increased after castration with Burdizzo, CaCl2 and Olive oil but were decreased by day 28 after castration.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The resolution of the post castration inflammation and associated swelling indicates healing of damaged tissue and cessation of spermatogenesis provided that the castration was successful. Testosterone production is usually affected as was previously reported that testosterone concentration was significantly decreased from 6.1 ng/ml on the day of castration to 0.6 ng/ml 30 days later (Al-Asadi and Al-Kadi 2012; Hasan et al 2016). As was observed for the testes, the diameters of the left and right spermatic cords also increased after castration with Burdizzo, CaCl2 and Olive oil but were decreased by day 28 after castration.…”
Section: Discussionmentioning
confidence: 54%
“…Castration involves the extirpation or suppression of gonadal function (Neto et al, 2014). Following orchiectomy in goats, serum testosterone concentration significantly (P < 0.01) decreased from 6.1 ± 0.2 ng/mL on the day of castration to 0.6 ± 0.0 ng/mL 30 days later (Hasan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After collection, the blood was centrifuged at 3000 rpm for 20 minutes to collect serum. Serum was collected in Eppendorf tubes and preserved at -20° C (Talukder et al, 2018;Hasan et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Funding for this work was provided by the Ministry of Science and Technology, Government of the People's Republic of Bangladesh through National Science and Technology Fellowship/2015-2016 (Grant No. 93.012.002.01.03.022-2015…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…A 3 mL blood sample was collected from the jugular vein daily with appropriate asceptic measures, without using any anticoagulant prior to ultrasonography. Then, serum was collected after centrifuging at 1,500 rpm for 15 min and stored at −80°C until determination by ELISA of the concentrations of progesterone and oestradiol hormone (17). The serum sample was equilibrated at room temperature for half an hour.…”
Section: Methodsmentioning
confidence: 99%